A synopsis of Coulteria (Leguminosae), including new names and synonyms - Sotuyo, Solange; Contreras, José Luis; Gagnon, Edeline; Lewis, Gwilym P. (Phytotaxa, 2017)
As a result of ongoing studies in Caesalpinia sensu lato, new combinations and synonyms are proposed in the reinstated segregate genus Coulteria.